OPTIMALISASI PRODUKSI KACANG TANAH DAN JAGUNG PADA POLA TANAM TUMPANGSARI DENGAN PERLAKUAN DEFOLIASI JAGUNG - Khodijah NS; Kusmiadi R; Sartika S (Enviagro: Jurnal Pertanian dan Lingkungan, 2014)
The purpose of this study was to determine the effect of defoliation in maize to the production of ground nut which grown on intercropped pattern with maize. The research was conducted from June until September 2012 in the Balunijuk village, Merawang subdistrict, Bangka Belitung. The experimental design used in randomized block design with 3 treatments, they were: without defoliation (control), and defoliation at 1 and 2 weeks after pollination in maize. The results showed that the maize defoliation treatment gives a better influence on plant height and weight of 100 seeds on ground nut than without defoliation. While the maize, defoliation treatments at 1 and 2 weeks after pollination could increase the number of cobs/maize.